PERCEPTIONS OF TEACHERS’ AND STUDENTS’ ON THE INTEGRATION OF ICT IN CHEMISTRYINSTRUCTION IN SENIOR SECONDARY SCHOOLS IN AWKA EDUCATION ZONE - Juliana Nkiru Nnoli; Uchenna Favour Muogbo (International Journal of Teaching and Learning, 2025)
This study aimed to ascertain the perception of teachers and students on the integration of ICT in teaching and learning of chemistry in senior secondary schools in Awka education zone. Descriptive survey research design was used to carry out this study. The population for this study consist of chemistry Teachers and Students in the 61 public secondary schools in Awka Education Zone of Anambra State. A sample size of 20 chemistry teachers and 130 senior secondary school chemistry students were used for the study. The simple random sampling method was used to select ten (10) out of the 61 public secondary schools. Hence, in each of the five local government area of Awka Education Zone, two public secondary schools were randomly selected. From the major aims of the study, five research questions were raised and answered to achieve the purpose of this study. The instrument used for collection of data was a structured questionnaire developed by the researchers. The questionnaires contain thirty-five (35) item questions. The instrument was validated by two (2) lecturers from the Department of Science Education and one from educational foundation, Nnamdi Azikiwe University, Awka. A reliability coefficient index of 0.73 was established using Cronbach Alpha statistics. Data for the study was collected by the researcher. Data collected were analyzed using mean and standard deviation. The mean was used to answer the research questions. Results revealed that ICT improves the quality of teaching and learning of chemistry in senior secondary schools. It was concluded that the utilization of ICT increases the interest of teachers and students towards chemistry. It was then recommended that adequate ICT equipments for teaching chemistry should be provided by the ministry of education and school management.